2018
DOI: 10.18632/oncotarget.25333
|View full text |Cite
|
Sign up to set email alerts
|

Association of TET3 epigenetic inactivation with head and neck cancer

Abstract: The aim of this study was to clarify the epigenetic regulation of ten eleven translocation protein (TET) family genes, which can provide insights into the mechanisms of tumorigenesis and the risk of disease recurrence in head and neck squamous cell carcinoma (HNSCC). We generated methylation profiles of TET1, TET2 and TET3 genes in tumor samples obtained from 233 patients with HNSCC; these included 57 hypopharynx, 44 larynx, 69 oral cavity, and 63 oropharynx tumor samples. The mRNA expression and promoter DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 50 publications
1
23
0
1
Order By: Relevance
“…DNA methylation is a frequent and key epigenetic mechanism underlying the regulation of processes associated with neoplastic transformation [38]. Recently, TET proteins have been identified as important epigenetic modifiers via their dioxygenase activity [39]. TET expression and activity are inhibited by genetic mutations and high methylation of their own promoters [40].…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is a frequent and key epigenetic mechanism underlying the regulation of processes associated with neoplastic transformation [38]. Recently, TET proteins have been identified as important epigenetic modifiers via their dioxygenase activity [39]. TET expression and activity are inhibited by genetic mutations and high methylation of their own promoters [40].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that reduced methyl donor was associated with increased expression of TET-1 in HPV-positive HNSCC cell line. The aberrantly methylated TET enzymes in HNSCC patients were studied by Misawa et al (2018a), who reported lower expression of TET-1 and TET-3 in HNSCC, while methylation level of these genes was higher in cancer cells, suggesting that downregulation of TET-1 and TET-3 must have been associated with their promoter methylation. Moreover, the multivariate analysis revealed that TET-3 methylation in OSCC and oropharyngeal cancer was connected with poor survival of HNSCC patients (Misawa et al 2018a).…”
Section: Tetmentioning
confidence: 99%
“…Dissociation curves were carried out at the end of each PCR by following a 3-step procedure. Analysis was performed using the software (version 1.03A) for the Thermal Cycler Dice Real Time System TP800 (TaKaRa), according to the manufacturer’s directions [33,34].…”
Section: Methodsmentioning
confidence: 99%